DEVELOPMENT OF CHEMICAL ON HOUSEHOLD INTERACTIVE MULTIMEDIA AND KIT FOR HEARING IMPAIRMENT STUDENTS OF JUNIOR HIGH SCHOOL FOR DISABILITIES - Sukarmin, Sukarmin (Universitas Negeri Surabaya, 2019)
This study aims to describe the feasibility of interactive multimedia and the developed kits, the activities of students, the understanding of students' concepts, and students' responses. Interactive multimedia and kits were developed with Writing to Learn strategies. Feasibility criteria consist of content, presentation, language, and graphics. This type of research was developed with the Research and Development (R & D) method. The research subjects are interactive multimedia and developed kits. The research instruments consisted of validation sheets, student activity observation sheets, concept understanding test sheets, and student response questionnaire sheets. Data sources were obtained from chemistry lecturers, Special Education lecturers, Special School teachers, and five students from Blitar State Special Junior High School. Data were analyzed descriptively. The results of the study show that interactive multimedia and kits are very feasible to be used as learning media with a percentage of eligibility ≥ 61%. Percentage of students student activities were in range 66,66% - 100% for each activities. Students’ score and Students’ concept understanding were increased after trial. The results of student responses indicate that interactive multimedia and kits get a positive response because they get a percentage of ≥ 61% for each aspects.